Diagnostic Accuracy of PET for Differentiating True Glioma Progression From Post Treatment-Related Changes: A Systematic Review and Meta-Analysis - Cui, Meng; Zorrilla-Veloz, Rocío Isabel; Hu, Jian; Guan, Bing; Ma, Xiaodong (Frontiers in Neurology, 2021)
Purpose To evaluate the diagnostic accuracy of PET with different radiotracers and parameters in differentiating between true glioma progression (TPR) and posttreatment-related change (PTRC). Methods Studies on using PET to differentiate between TPR and PTRC were screened from the PubMed and Embase databases. By following the PRISMA checklist, the quality assessment of included studies was performed, the true positive and negative values (TP and TN), false positive and negative values (FP and FN) and general characteristics of all the included studies were extracted. Results of PET consistent with reference standard were defined as TP or TN. The pooled sensitivity (Sen), specificity (Spe), and hierarchical summary receiver operating characteristic curves (HSROC) were generated to evaluate the diagnostic accuracy. Results The 33 included studies had 1734 patients with 1811 lesions suspected of glioma recurrence. Fifteen studies tested the accuracy of 18F-FET PET, 12 tested 18F-FDG PET, 7 tested 11C-MET PET, 3 tested 18F-DOPA PET. 18F-FET PET showed a pooled Sen and Spe of 0.88 (95% CI: 0.80, 0.93) and 0.78 (0.69, 0.85), respectively. In the subgroup analysis of FET-PET, diagnostic accuracy of high grade gliomas (HGGs) was higher than that of mixed grades gliomas (Pinteraction=0.04). 18F-FDG PET showed a pooled Sen and Spe of 0.78 (95% CI: 0.71, 0.83) and 0.87 (0.80, 0.92), the Spe of HGGs group was lower than that of low grade gliomas group (0.82 versus 0.90, P=0.02). 11C-MET PET had a pooled Sen and Spe of 0.92 (95% CI: 0.83, 0.96) and 0.78 (0.69, 0.86). 18F-DOPA PET had a pooled Sen and Spe of 0.85 (95% CI: 0.80, 0.89) and 0.70 (0.60, 0.79). FET-PET combined with MRI had a pooled Sen and Spe of 0.88 (95% CI: 0.78, 0.94) and 0.76 (0.57, 0.88). Multi-parameters analysis of FET-PET had pooled Sen and Spe values of 0.88 (95% CI: 0.81, 0.92) and 0.79 (0.63, 0.89). Conclusion PET has a moderate diagnostic accuracy in differentiating between TPR and PTRC. The high Sen of amino acid PET and high Spe of FDG-PET suggest that the combination of commonly use FET-PET and FDG-PET may be more accurate and promising, especially for low-grade glioma.